Reestructuración capitalista bajo el neoliberalismo: Desarrollo y debacle industrial en Argentina en los '90 - Sebastián P. Salvia (Atlantic Review of Economics (ARoEc), 2018)
– This article approaches to the transformations of the manufacturing industry in Argentina in the nineties. These transformations took place within the framework of a profound capitalist restructuring, promoted by the process of neoliberal reforms carried out by the Argentine State. As happened in different countries of the region, although with a particular way in Argentina, these reforms were based on an increase in trade liberalization, labor flexibilization laws, economic deregulation, privatizations of State companies, etc. These reforms were accompanied by an extremely restrictive monetary policy, which greatest exponent was the fixing of the exchange rate by State Law, an argentinean peculiarity. In this sense, the work discusses with prominent authors that characterize the nineties as a period of "deindustrialization". We developed a methodology for the quantitative analysis of official information, produced by the Center for Studies for Production (CEP), the Ministry of Economy, the Central Bank of the Argentine Republic (BCRA) and the National Institute. of Statistics and Census (INDEC). We focus on information related to the manufacturing industry on productivity and product, employment, real salary and profitability. In the same way, we use information on social indicators such as unemployment and underemployment, levels of poverty and indigence, etc. From this, we found that the capitalist restructuring had a strong impact on the manufacturing industry, which became one of the motors of the productive reconversion. In the ascending phase of this process in 1991-98, the industry increased its competitiveness, with an accelerated growth in industrial productivity, a notable increase in output and an expansion in profitability, at the same time as real wages stagnated and grew social inequality. This expansive moment was also uneven among industrial subsectors. In the downward phase of this process in 1999-2001, gains in industrial competitiveness tended to fade. The industry led the economic meltdown, leading to lower profitability, employment and product, while productivity stagnated. The debacle took to its maximum the deterioration of the conditions of the working class, with unprecedented levels of unemployment, poverty and indigence in the country. Consequently, the result of capitalist restructuring under neoliberalism was a process of accelerated economic growth with a strong negative impact in social terms, amplified dramatically in the final crisis of the period
Keywords: N66; 330; Industry; Restructuring; Neoliberalism; Competitiveness; Crisis